Three-dimensional finite element simulation of high speed milling of titanium alloy Ti6Al4V. Issue 1 (June 2021) - Wang, Zhenda; Ze, Xiangbo; Yousuf, Yusuf Abudllahi; Jiang, Zhenfeng; Fu, Xiuli; Pan, Yongzhi
Abstract: In this paper, ABAQUS finite element simulation software was used to establish a more reliable three-dimensional milling titanium alloy Ti6Al4V finite element simulation model. This model sets up important links such as the material constitutive model, the tool-chip contact friction model, and the chip separation criterion. And the accuracy of the model is verified by experiments. Based on this model, orthogonal experiment was used to explore the effects of axial cutting depth, tool speed and feed speed on the milling force. And the morphology of the chip and the surface morphology of the machined workpiece were investigated. The results show that the influence of cutting parameters on milling force from high to low is as follows: axial cutting depth > tool speed > feed rate. The change of cutting parameters has different influence on milling force in all directions, and has the largest influence on milling force in X direction.